Influences of cobalt dopant on the phases, microstructures and dielectric properties of PZT ceramics - B. Cherdhirunkorn (2018)
The effects of cobalt dopant on the properties of PZT ceramics with the formula of Pb(Zr0.52Ti0.48)1-xCoxO3 (where x = 0, 0. 002, 0. 005, 0. 01, 0. 015. 0. 02, 0. 025 and 0. 03) were studied. The cobalt doped PZT ceramics were produced using a conventional mixed oxides route. Phase structure and microstructure of these PZT ceramics were investigated using XRD and SEM techniques. The XRD spectra of the cobalt doped PZT ceramics showed that the higher level of cobalt incorporated into PZT ceramics could shift the MPB toward the rhombohedral phase region of the PbZrO3-PbTiO3 phase diagram. The SEM images revealed that cobalt acted as a grain growth inhibitor. Furthermore, the solubility limit of cobalt in PZT ceramics seemed to be less than 3mol%, since a second phase (cobalt-rich phase) was detected at the grain boundary. The P-E loops and dielectric properties of cobalt doped PZT ceramics were measured at high ac electric field in the range of 0. 2 to 2kVmm-1. An increase of the Curie point was also observed in cobalt doped PZT ceramics.